2007
DOI: 10.1186/1471-2164-8-289
|View full text |Cite
|
Sign up to set email alerts
|

GntR family of regulators in Mycobacterium smegmatis: a sequence and structure based characterization

Abstract: Background: Mycobacterium smegmatis is fast growing non-pathogenic mycobacteria. This organism has been widely used as a model organism to study the biology of other virulent and extremely slow growing species like Mycobacterium tuberculosis. Based on the homology of the Nterminal DNA binding domain, the recently sequenced genome of M. smegmatis has been shown to possess several putative GntR regulators. A striking characteristic feature of this family of regulators is that they possess a conserved N-terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…GntR family members had an annotated GntR-type DNA-binding domain (IPR000524). Diverse regulators from the GntR family were divided into three subfamilies according to the previously described classification (17).…”
Section: Methodsmentioning
confidence: 99%
“…GntR family members had an annotated GntR-type DNA-binding domain (IPR000524). Diverse regulators from the GntR family were divided into three subfamilies according to the previously described classification (17).…”
Section: Methodsmentioning
confidence: 99%
“…Previous in silico sequence analysis of RoxY indicated that it belongs to the FadR subfamily of GntR regulators (39). GntR family regulators are often autoregulatory and found adjacent to genes that they control (15).…”
Section: Discussionmentioning
confidence: 99%
“…Upstream region of mce2R possess novel conserved operator site Many FadR-like transcriptional regulators are reported to recognize DNA palindromes showing nucleotide preferences exhibited by members of FadR subfamily [9]. We analyzed DNA sequences for these preferences, in addition to conservation among the orthologous upstream region.…”
Section: Rv0586-orthologs Show a Similar Dna Binding Domainmentioning
confidence: 99%
“…Out of five FadRlike transcriptional regulators from M. tuberculosis, the regulators Rv0165c and Rv0586 are associated with mce1 and mce2 operon, respectively [7,8]. Typically, members of this subfamily of transcriptional regulators are known to be auto-regulatory [9]. Hence in addition to regulating expression of a number of genes and operons these regulators also regulate their own expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation